Water management and food production in China and India: a comparative assessment - Cai, Ximing; Rosegrant, Mark W. (IWA Publishing, 2005)
China and India have different climatic and hydrologic features, which characterize their agricultural production; they have experienced different water resources development in supporting their agriculture. In this paper, we try to indicate diversified water management strategies for China and India based on comparisons between the two countries. We also address their common problems and perspectives in water management and agriculture. This paper concludes that China's major challenge is to improve irrigation by more efficient use of water. On the other hand, India may have a greater potential in irrigating more land, improving rainfed crop yields, as well as creating efficient use of water.